Estudio comparativo de los ingresos dentro del periodo 2020-2021 de la compañía de transporte en camionetas mixta Giovanni Bravo "TRANSGIOVANBRA S.A." - Herdoiza Salazar, Iván Josué (2022)
The importance of the transport industry in Ecuador is closely related to the development of other productive activities, the commitment of this service depends not only on the progress of the applicant, but also on the capacity of the companies that provide this occupation. The present case study consists of the analysis and comparison study of the income of the 2020 - 2021 period of the mixed van transport company Giovanni Bravo through the interpretation of the financial statements and financial ratios that allowed a better observation of how the company is financially located. The comparative and inductive method was used to make general conclusions according to the data obtained. The elaboration of this project was achieved thanks to the information such as the statements of financial position and statements of results of said periods provided by the entity.